Loss of heterozygosity at 9p and p53 immunopositivity in surgical margins predict local relapse in head and neck squamous cell carcinoma - Graveland, A. Peggy; Golusinski, Pawel J.; Buijze, Marijke; Douma, Rinze; Sons, Nanet; Kuik, Dirk J.; Bloemena, Elisabeth; Leemans, C. René; Brakenhoff, Ruud H.; Braakhuis, Boudewijn J.M. (International journal of cancer, 2011)
A major problem in head and neck cancer surgery is the high rate of local relapse (LR). In at least 25% of the surgically treated head and neck squamous cell carcinoma (HNSCC) patients, a genetically defined preneoplastic lesion, also known as “field,” can be detected in the surgical margins. A remaining field may be an important cause for the development of LR. The aims of our study are (i) to investigate whether HNSCC patients with an unresected field are more likely to develop LR, and (ii) to identify molecular risk factors that predict malignant transformation of field. We retrospectively studied 35 HNSCC patients of whom 16 patients developed LR and 19 patients remained disease‐free for at least 4 years. Loss of heterozygosity (LOH) at chromosomes 3p, 9p and 17p, p53 immunostaining, Ki‐67 immunostaining and histopathological grading of all available paraffin‐embedded surgical margins was performed, and related to LR. Significant associations were determined by Kaplan‐Meier analysis and Cox‐proportional hazard models. We show that presence of field is significantly associated with LR and that LOH at 9p and p53 immunostaining have the most predictive potential (hazard ratios 3.17 and 3.46, and p values 0.027 and 0.017, respectively). The combination of LOH at 9p and/or a large p53 positive field is most predictive (hazard ratio 7.06 and p = 0.01). Presence and grade of dysplasia was not associated with LR. These data may have major impact for future diagnostic workup of surgically treated HNSCC patients.